(untitled) (ModaPalavra e-periódico, 2014)
The study aims to analyze the actions of luxury fashion brands within the social network Facebook. For that, based on the report of the year 2012 Branz-identified the three most valuable brands in the luxury sector: Louis Vuitton, Hermès and Gucci. The study was conducted by monitoring the fan pages of these brands. As results, we note that there is no incentive for users to engage in a dialogue, the basic assumption of this communication platform. Consequently, the main character ends up taking a virtual catalog, since the main actions are the posts related to promotion of products and campaigns.